A Comparative Study Of Occupational Stress And Associated Risk Factors Among Primary And Secondary School Teachers - Siti Hawa, Bohari (2025)
Teaching is usually acknowledged as one of the most stressful professions because facing a various challenges lead to significantly impact on their emotional and physical health. This cross-sectional study is conducted to measure the level of stress, to compare the level of stress and to determine the risk factors associated with stress among primary and secondary school teachers in the district of Jasin, Melaka. About 75 completed questionnaires were returned from primary school teachers and only 65 questionnaires from secondary school teachers. This quantitative study used Depression Anxiety and Stress 21 items Questionnaire (DASS 21) Malay version to measure the level of stress while Work Stressor Questionnaire from American Institute for Preventive Medicine is adapted to identify work stressor among the teachers both types of school which consist of 11 items. Statistical Package for Social Science (SPSS) version 27 is used to analyse all the data of questionnaires that collected during the data collection. Results showed that most of primary school teachers (77.3%) had normal stress levels, while secondary school teacher has wide range of levels of stress (mild = 20%, moderate = 15.4%, severe = 1.5%). Mann-Whitney Test showed significant difference in stress levels (pvalue= 0.034) between primary and secondary school teachers. The result of the Spearman correlation analysis revealed that Pressure on the Job (p = 0.028) is the only risk factor that influence the stress levels among secondary school teachers. While the result of the Fisher-Freeman-Halton Exact test showed level of education has significant association with stress levels among primary school teachers (p<.001). In conclusion, teachers should get regular stress management training to help them develop appropriate coping mechanisms, especially for dealing with job-related stresses.